RISK FACTORS OF GLAUCOMA DISEASE AMONG PATIENTS ATTENDING GLAUCOMA COUNSELLING HEALTH FACILITY AT KWARA STATE SPECIALIST HOSPITAL, SOBI, ILORIN, NIGERIA - Ibrahim Ologele; Basirat Omolola Sulaiman (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
: Glaucoma is a disease that damages the optic nerve and is a principal cause of vision loss throughout the world. Therefore, this study investigated the risk factors of glaucoma disease among patients attending glaucoma counselling health facility at Kwara State Specialist Hospital Sobi, Ilorin, Nigeria. A descriptive research design of survey type was used. Close-ended questionnaire was used for the data collection. The instrument used for the study was validated by using three specialists in the related fields. A reliability co-efficient of 0.75r was obtained through test-retest technique using Pearson Product Moment Correlation. The  hypotheses raised had been examined using the inferential statistics of Chi-square at 0.05 alpha level of significance. The findings of the study confirmed that hereditary, consumption of poor diet and drug abuse  were the risk factors for glaucoma disease among patiens attending glaucoma counseling centres. The researchers concluded that the  patients attending glaucoma counselling health facility surfer from the condition due to glaucoma sickness that runs in their families, excessive consumption of salt, excessive consumption of coffee and caffeinated beverages, day by day consumption of cigarette and use of unprescribed eyes drops. The researchers recommends that there is need for health officers to enlighten the patients attending glaucoma counselling health facility on the benefits of advising their households members particularly those above 30 years of age to undergo comprehensive eye dilation examination  to forestall vision loss which cause through glaucoma disorder.